Peer assisted academic support: a comparison of mentors' and mentees' experiences of a drop-in programme. Issue 9 (21st October 2021) - Garcia-Melgar, Ana; East, Julianne; Meyers, Noel
ABSTRACT: In Peer Assisted Learning (PAL) programmes, students provide academic and social support to fellow students. Recent PAL iterations include drop-in programmes to improve higher education students' general academic literacy in an open, non-judgemental, learning environment led by experienced students. The majority of the PAL literature, however, focuses on curricular programmes, with limited understandings on processes enabling positive outcomes for students. This study contributes to the PAL literature through the investigation of factors and mentoring strategies underpinning effective peer learning in drop-in PAL programmes. Participants were students attending an academic drop-in PAL programme, and the peer mentors employed by the programme. Results suggest that students' expectations about the type of support provided by PAL mentors may jeopardise the learning objectives of the programme. The analysis of PAL mentors' experiences reveals how the use of strategies to enhance social and cognitive congruence between peers supports the development of effective peer learning partnerships. Mentors' approachability alongside their ability to provide practical strategies and academic examples tailored to students' learning needs characterised peer learning interactions between students. Mentors also encouraged students to engage in active help-seeking behaviours. This paper examines strategies to enhance peer learning interactions that support the development of independent and transferable academic skills in students seeking peer support.